Republic of Latvia : 2012 Article IV Consultation and Second Post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report ;, 2013)
Latvia has rebounded from the crisis, after successfully undertaking a difficult adjustment program. The recovery has been well balanced between external and domestic demand. The labor market is improving but unemployment is still high. Past consolidation efforts have brought down the fiscal deficit. The banking system is recovering. Nonresident deposits in the banking system have been expanding rapidly. Economic growth is expected to weaken slightly in 2013, before picking up later. Euro adoption in 2014 appears within reach, subject to some technical uncertainties.